The Impact of Local Attitudes on the Development of Health Tourism - Mahboobeh Asadzadeh; Soudabeh Vatankhah; Aidin Aryankhesal (Indian Journal of Forensic Medicine & Toxicology, 2022)
Introduction: Marketing techniques such as positive imaging of health tourism destinations can be a powerful tool in attracting users of health tourism services. The presence of satisfied citizens who create a stable identity for the city and strongly defend the city’s brand can guarantee the success of branding programs.The aim of this study was to identify the effect of local attitudes of citizens about development of health tourism in their city and offer suggestions to improve attitudes and align the interests of citizens as stakeholders in this industry.Methods: we have used aqualitative approach based on conventional content analysis by semi-structured interviews. Content analysis was used as a systematic method to describe a specificphenomenonin-depth, which leads to revision, valid conclusions from information, and the production of new knowledge and insights, and to examine people’s experiences and attitudes toward the specific subject.Results: The results of the analysis of interview data revealed three main themes include hygiene concerns, economic concerns, and safety concerns.Conclusion: According to the concerns of citizens extracted from this study, it is suggested that policy makers in the field of health tourism, along with other relevant organs and organizations, take steps to plan to reduce this concerns. In regard to provide,health services tourism attractionsby supporting citizens in creating a positive image of destination.